An Analytical Evaluation of the Synergistic Effect on Biodiesel Oxidation Stability Promoted by Binary and Ternary Blends Containing Multifunctional Additives - Silvia S. Yahagi; Ana C. Roveda; Adrielli T. Sobral; Ivan P. Oliveira; Anderson R. L. Caires; Roberto S. Gomes; Magno A. G. Trindade (International Journal of Analytical Chemistry)
The antioxidant potential of a novel additive, named maleimide p-CH3, and the synergistic effect on biodiesel stabilization when combined with a traditional synthetic antioxidant (e.g., propyl gallate (PG)) as well as alternative additives (e.g., alizarin (ALZ) and citric acid (CA)) were investigated. The additives were combined in binary and/or ternary blends at low concentrations and their effectiveness against soybean biodiesel oxidation in the absence and presence of metal was tested. The effectiveness of binary and ternary blends was also evaluated by the Rancimat® method and compared with total acid number (TAN). The results showed that the combinations presented synergetic effects and were effective in stabilizing biodiesel in accordance with the minimum requirements of EN 14214 and also revealed that the mixture containing PG and p-CH3, even at low concentrations, can be successfully applied for biodiesel preservation. In summary, we report that the biodiesel stability can be obtained by using a reduced amount of additives, suggesting that biodiesel shelf life can be improved in association with a cost reduction when compared to the use of conventional antioxidants.